EVALUASI KEBIJAKAN MANAJEMEN ASN DITINJAU DARI ASPEK PERENCANAAN, PEREKRUTAN DAN PENGEMBANGAN KOMPETENSI DI KEMENTERIAN PERHUBUNGAN REPUBLIK INDONESIA - Robby Kurniawan; Aries Djaenuri; Hadi Prabowo; Sampara Lukman (GoAcademica Research dan Publishing, 2020)
This study aims to evaluate ASN management policies at the Ministry of Transportation in terms of planning, recruitment and potential development. The approach used in this study is to use action research-based Soft Systems Methodology (SSM) as a research method with a systems thinking approach. The selection of this research method was carried out considering that ASN management is a Human Activity System with various problems involving many agencies and there are various laws and regulations that are used. The results of the study found a problematic situation in ASN management policies in the aspects of planning, recruitment, and competency development. Management evaluation uses 7 dimensions and indicators which include: policy, its formulation, and dissemination, social, political and economic context, leadership for policy implementation, stakeholder involvement in policy implementation, planning implementation and resource mobilization, operations and services, and feedback on progress and results.